The HMS Defender incident: innocent passage versus belligerent rights in the Black Sea - Turns, David (American Society of International Law, 2021)
On June 23, 2021, the United Kingdom Royal Navy destroyer HMS Defender, detached to the Black Sea on "its own [unspecified] set of missions" from a Carrier Strike Group (CSG) in the Mediterranean, was en route from Odessa, Ukraine, to Batumi, Georgia, when she passed approximately nine kilometres off Cape Fiolent on the southwest coast of Crimea. What happened next depends on which account one chooses to believe. According to the Russian Ministry of Defence, a "[Black Sea Fleet] border guard patrol ship conducted warning fire . . . [and] a Su-24M plane carried out preventing [sic] bombing (four OFAB-250 bombs) along the route of . . . Defender."[1] In a written statement to the House of Commons the next day, the British Secretary of State for Defence specified that, a Russian coastguard vessel warned that Russian units would shortly commence a live fire gunnery exercise . . . HMS Defender noted gunnery astern and out of range of her position. This posed no danger to HMS Defender. During her transit, HMS Defender was overflown by Russian combat aircraft at varying heights, the lowest of which was approximately 500 feet. These aircraft posed no immediate threat to HMS Defender . . . .[2] These competing factual accounts have dominated most of the coverage of the incident, but there has been comparatively little reference to the territorial status of Crimea (which has been in dispute since 2014), and it is notable that the international law arguments used (explicitly or implicitly) differ markedly in doctrinal emphasis, even when one passes over the rhetorical grandstanding. This short article evaluates the June 23 incident at the intersection of the two bodies of international law that are principally relevant: the international law of the sea and the international law of armed conflict.
Keywords: belligerent occupation; territorial sea; humanitarian law; maritime law; International law